Long-Term Weight Outcomes after Bariatric Surgery: A Single Center Saudi Arabian Cohort Experience - Assim A. Alfadda (MDPI AG, 2021)
Background: Obesity is considered a global chronic disease requiring weight management through lifestyle modification, pharmacotherapy, or weight loss surgery. The dramatic increase in patients with severe obesity in Saudi Arabia is paralleled with those undergoing bariatric surgery. Although known to be beneficial in the short term, the long-term impacts of surgery within this group and the sustainability of weight loss after surgery remains unclear. Objectives: We aimed to assess the long-term weight outcomes after bariatric surgery. Setting: The study was conducted at King Khalid University Hospital (KKUH), King Saud University Medical City (KSUMC) in Riyadh, Saudi Arabia. Methods: An observational prospective cohort study on adult patients with severe obesity undergoing bariatric surgery (sleeve gastrectomy (SG) or Roux-en Y gastric bypass (RYGB)) during the period between 2009 and 2015 was conducted. Weight loss patterns were evaluated pre- and post-surgery through clinical and anthropometric assessments. Absolute weight loss was determined, and outcome variables: percent excess weight loss (%EWL), percent total weight loss (%TWL), and percent weight regain (%WR), were calculated. Statistical analysis using univariate and multivariate general linear modelling was carried out. Results: A total of 91 (46 males and 45 females) patients were included in the study, with the majority belonging to the SG group. Significant weight reductions were observed at 1 and 3 years of follow-up (p < 0.001) from baseline. The %EWL and %TWL were at their maximum at 3 years (72.4% and 75.8%) and were comparable between the SG and RYGB. Decrements in %EWL and %TWL and increases in %WR were seen from 3 years onwards from bariatric surgery until the study period ended. The yearly follow-up attrition rate was 20.8% at 1 year post-surgery, 26.4% at year 2, 31.8% at year 3, 47.3% at year 4, 62.6% at year 5, and 79.1% at end of study period (at year 6). Conclusion: The major challenge to the successful outcome of bariatric surgery is in maintaining weight loss in the long-term and minimizing weight regain. Factors such as the type of surgery and gender need to be considered before and after surgery, with an emphasis on the need for long-term follow-up to enssure the optimal benefits from this intervention.